The Rolling Stones in concert, 1962/1982 : a show-by-show history - Rusten, Ian (McFarland & Company, 2018)
"This day-by-day chronicle of every live concert by the Rolling Stones from 1962 through 1982. Comprehensive coverage of the shows includes set lists, venues, concert reviews, anecdotes and notable events in the lives of the band members. A list of their radio recordings, television performances, never-before-published posters, programs, tickets, handbills and photographs is included"--